Ventricular Cerebrospinal Fluid Sampling in Pediatric Diffuse Midline Glioma Patients: Institutional Experience and Review of the Literature - Li, Daphne; Stellpflug, Wendy; Romanski, Kathy; Kilgallon, Maureen; Speck, Stacy; Saratsis, Amanda M. (Frontiers in Pediatrics, 2020)
Purpose Increasing evidence suggests that circulating biomarkers may serve diagnostic and longitudinal monitoring purposes in pediatric neuro-oncology. Mutant tumor DNA is detectable in the cerebrospinal fluid (CSF) of pediatric diffuse midline glioma (DMG) patients and quantity can reflect disease burden. CSF sampling (“liquid biopsy”) via a CSF access device could therefore play a role in DMG management. Therefore, we set to evaluate the incidence of hydrocephalus (HCP) in DMG patients, and to characterize ventricular reservoir placement and access practices. Methods A single institution retrospective review of DMG patients <21-years-old was performed (1984-2019). MEDLINE searches for reports of ventricular reservoir or shunt placement in DMG, and reservoir access for intraventricular chemotherapy (IVC) were performed. Results At our institution, 62.6% of DMG patients (67/108) required intervention for HCP: 19.4% provided transient CSF access (ETV alone n=3, EVD n=8, unspecified n=2), and 80.6% permanent CSF access (ETV + reservoir n=13, shunt n=41). Further, 22/34 patients with initially transient CSF devices required conversion to a permanent device. Five devices were revised for malfunction, one for infection. Seventeen articles cited HCP in 22% to 100% of DMG patients. IVC administration was described in 632 patients (seven articles), with 42 infectious and 63 non-infectious complications. Conclusions Management of HCP is often necessary in children with DMG. Given the low rate of clinical risk associated with VAD placement and access, and the potential utility of longitudinal disease monitoring via CSF analysis, VAD placement could be considered in future clinical trials to guide DMG treatment.